Unique attributes of internet TV in enhancing students' learning experience / Dzaa Imma Abdul Latiff ...[et al.] - Abdul Latiff, Dzaa Imma; Yasin, Megat Al-Imran; Abdullah, Siti Nur Fadzilah; Hassan, Amira; Md Noor, Mohd Faisal; Mohammad Roshdan, Nur Faathinah (Faculty of Communication and Media Studies, Universiti Teknologi MARA, 2019)
Internet TV as a mobile entertainment has become an interesting medium in creating awareness on news and current issues to the public. Nowadays the traditional television which only allows audiences to be at one specific place has contributed to Internet TV use. Besides, the expensive cost of technology such as money value may contribute to barriers to integrate with higher learning obligations. Currently, Internet TV in Malaysia is focused mostly on business and technology impact. Few studies have been conducted on specific attributes of Internet TV as the factors that influence students to adopt. The unique characteristics (content, cost, monetary and technology) of Internet TV may play a vital task in formulating the user's expectation of Internet TV. Thus, this paper studies specific attributes of Internet TV in enhancing students' learning experience. A modified framework of previous research on new technology adoption such as the internet, smartphones, and IPTV was used to explore the exogenous variables that influenced students to adopt. A total of 518 respondents were selected among the undergraduate students via online survey which were analyzed through covariance-based structural equation modeling. The findings supported the idea that specific attributes of Internet TV, give impact to students' intention to use as part of the medium in learning. Results of the hypotheses showed a positive and significant effect towards the Internet TV adoption on TV news. The results also improved our knowledge and understanding in a mission to inform that Internet TV can be part of the educational approach in teaching and learning. In conclusion, the innovation technology framework is a good theoretical medium to understand factors that influence students to adopt Internet TV on news and current issues. This study is both beneficial and significant for the researchers, educators, media practitioners, and public in order to keep modern technology and education in line.